Analisis Kemampuan Pemecahan Masalah Matematis Siswa dalam Menyelesaikan Soal TIMSS Materi Geometri - Aditya Kusuma Wardhani; Haerudin; Ramlah (Didactical Mathematics, 2022)
This study aims to analyze the mathematical problem solving ability of students in working on TIMSS questions on geometry material. This qualitative study using student subjects aged 13─15 years as many as 5 students were selected by purposive sampling.The analytical technique used is descriptive analysis, the data from the problem solving ability test results are analyzed using a problem-solving assessment rubric that has been determined by referring to the problem-solving steps according to Polya. The results showed that the re-examination stage is the stage that is most often forgotten as a result, errors often occur both in the results of the settlement and the formula used. So it can be concluded that the students mathematical problem solving ability in solving the TIMSS questions on geometry material is quite good.